CUSTOMER PREFERENCES FOR IB HASANAH CARD PRODUCTS AS FINANCIAL CARD AT BNI SYARIAH BANK SURABAYA BRANCH - Andro Agil Nur Rakhmad; Kurniawati Meylianingrum (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
Currently, the Islamic finance industry is proliferating and continues to make exciting innovations to attract customers. This innovation offers convenience and efficiency in financing Islamic banking in Indonesia. one of the product innovations offered is a sharia credit card. Unlike conventional banks' credit cards, which based on interest, this Islamic credit card still based on a contract. This study aims to look at the preferences of sharia bank customers, especially at the Surabaya branch of BNI Syariah bank, in using the iB hasanah card product. The method used in this study is a quantitative method with an explanatory approach. This study indicates that contracts, fines, fees, and services together have a positive effect on customer preferences in choosing the iB Hasanah Card product. Furthermore, each variable significantly affects customer preferences in choosing the IB Hasanah Card as an efficient payment card.